An Analysis of English Writers’ Perception about Thesaurus Program - Lidia Lali Momo; Maria Wilda Malo; Yutira Rambu Pata; Debora Soli Poro; Lusia Leilu Kaka (Didaktika: Jurnal Kependidikan, 2024)
As the learners of foreign language the writers from Indonesia need more practice in applying their competence in English. Writing in English is a big challenge for every writers that are original Indonesia. Writing is a process of continuing discovery. As they write, they may suddenly switch direction or double back. Because writing is a skill, it makes sense that the writers have to practice their skill to get more ideas. This research aims to find the writer’s reason in Waikabubak, Sumba Barat about thesaurus program. It tends a qualitative method and interview some teachers who like writing. Based on the result through the interview of some English teachers, the Thesaurus program is really helpful, provide so many variety words, thus the writers are really easy to find the appropriate word to use in their writing and avoid the plagiarism. This program assists the English teachers also in teaching synonim in variet words. The English writers implies also about this program, that this program can help the English teachers in teaching synonyms and antonyms by applying this program. The students are easy to know the new words from this program and are easy to understand that has been classified by noun, adjective and adjective.